Possible mechanism of metabolic and drug resistance with L-asparaginase therapy in childhood leukaemia - Zhou, Ruizhi; Liang, Tianqi; Li, Tianwen; Huang, Junbin; Chen, Chun (Frontiers in Oncology, 2023)
L-asparaginase, which hydrolyzes asparagine into aspartic acid and ammonia, is frequently used to treat acute lymphoblastic leukaemia in children. When combined with other chemotherapy drugs, the event-free survival rate is 90%. Due to immunogenicity and drug resistance, however, not all patients benefit from it, restricting the use of L-asparaginase therapy in other haematological cancers. To solve the problem of immunogenicity, several L-ASNase variants have emerged, such as Erwinia-ASNase and PEG-ASNase. However, even when Erwinia-ASNase is used as a substitute for E. coli-ASNase or PEG-ASNase, allergic reactions occur in 3%-33% of patients. All of these factors contributed to the development of novel L-ASNases. Additionally, L-ASNase resistance mechanisms, such as the methylation status of ASNS promoters and activation of autophagy, have further emphasized the importance of personalized treatment for paediatric haematological neoplasms. In this review, we discussed the metabolic effects of L-ASNase, mechanisms of drug resistance, applications in non-ALL leukaemia, and the development of novel L-ASNase.